Feasibility Analysis of Items for End of Semester Assesment Questions Class VII Indonesian Subjects of SMPN 1 Ngaglik - Nur Fitriyani; Hartono (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
This research is to determine the feasibility of the test items on the Indonesian language PAS questions for class VII at SMP Negeri 1 Ngaglik for the 2021/2022 academic year usingdocument analysis research with a quantitative descriptive approach. Sources of research data, namely the test questions grid, PAS question sheets in the form of student responses. The research subjects were 32 class VII B students at Ngaglik 1 Public Middle School for the 2021/2022 academic year. The research variable is the feasibility of the Indonesian PAS questions which consist of 40 questions. The research instruments were in the form of documentation guidelines, documentation collection techniques, and data analysis techniques in this study using descriptive statistical techniques. The research results show(1) validity level of 40 questions100% valid, (2) the reliability of the test items was 0.807 and declared reliable, (3) ITK, namely there were 6 easy questions, 30 moderate questions, 3 difficult questions, and 1 very difficult question; IDB there are 27 questions that are appropriate and 13 questions that are not feasible. (4) distractor analysis, there are 30 items (92.5%) that have very good distractor quality and 3 items (7.5%) that have poor distractor quality.